Pengolahan lateks pekat proses dadih menggunakan garam alginat hasil ekstraksi rumput laut untuk produk busa - Chasri Nurhayati; Oktavia Andayani (Balai Riset dan Standardisasi Industri Palembang, 2015)
Processing of concentrated latex derived from latex plantations using curd system is one of the concentrated latex processing as an alternative raw material for processing latex foam instead of using centrifuges. Generally concentrated latex used as raw materials processing foam products. Processing pendadihan is done by mixing the latex pendadih with gardens that have been preserved and left mendadih for a certain time. Concentrated latex concentration by means pendadihan require pendadih materials such as sodium alginate extracted from seaweed. The method of research using experimental design with of three variable concentrations of sodium alginate (K1) is the concentration of 0.15% The K2 = 0.20% concentration and K3 = 0.25% concentration. The results of testing the curd latex include dry rubber content (KKK), the levels of solids (KJP), ammonia and mechanical stability once every two days for 16 days. Curd result have been made of latex foam rubber products, further testing for hardness, tensile strength, elongation at break, pampatan fixed and specific gravity. The test results compared with foam rubber SNI number 1241-85. The results showed that the best latex curd is K2 with the value of the KKK: 52.03%, KJP: 54.02%, ammonia levels: 0.63% and mechanical stability:115 seconds and foam rubber products is best treated with violence K2:33 N/mm, tensile strength: 0,067 N/mm2, the value of elongation at break: 80%, the value of fixed pampatan: 18.63% and density: 0,143 g/cm3.Keywords : foam rubber, latex whey, natrium alginateAbstrakPenelitian ini bertujuan untuk mempelajari alternatif bahan pendadih yang berasal dari ekstraksi Sargasum sp. Penelitian dilakukan melalui 3 rangkaian tahapan yaitu ekstraksi natrium alginat dari Sargassum sp, penggunaan natrium alginat pada pendadihan lateks dan pembuatan karet busa menggunakan lateks dadih tersebut. Metode penelitian menggunakan desain eksperimental dengan 3 (tiga) variabel konsentrasi natrium alginat (K) yaitu K1= konsentrasi 0,15%, K2= konsentrasi 0,20% dan K3= konsentrasi 0,25%. Hasil lateks dadih dilakukan pengujian meliputi kadar karet kering (KKK), kadar jumlah padatan (KJP), kadar amonia dan kemantapan mekanik setiap dua hari sekali selama 16 hari. Lateks dadih yang dihasilkan dibuat produk karet busa, selanjutnya dilakukan pengujian terhadap kekerasan, tegangan putus, perpanjangan putus, pampatan tetap dan bobot jenis. Hasil pengujian dibandingkan dengan SNI karet busa 06-0999-1987. Hasil penelitian menunjukkan bahwa lateks dadih terbaik adalah perlakuan K2 dengan nilai KKK: 52,03%, KJP: 54,02%, kadar amonia: 0,63% dan kemantapan mekanik: 115 detik dan produk karet busa yang terbaik adalah perlakuan K2 dengan kekerasan: 33 N/mm, tegangan putus:0,067 N/mm2, nilai perpanjangan putus: 80%, nilai pampatan tetap: 18,63% dan berat jenis: 0,143 g/cm3.Kata Kunci : karet busa, lateks dadih, natrium alginat